TRANSLATION ANALYSIS BASED ON A SERIES “FRIENDS (1994): THE ONES WITH THE WHOLE GANG FROM” SEASON 1 - Hayuwanti, Hanifira; Krisdiyanta, Nugraha; Setiarini, Sri Endah (Conscientia - Journal on Language, Literature, and Culture, 2025)
This research examines the quality of Indonesian subtitles in the television series Friends (1994), focusing on the episode “The Ones with the Whole Gang” from Season 1. Using a qualitative descriptive approach with content analysis, the research analyzes ten selected subtitle excerpts to identify translation problems and evaluate applied strategies. The analysis is based on Dynamic Equivalence Theory (Nida, 1964), Skopos Theory (Vermeer, 1989), and the functionalist approach to audiovisual translation. The findings indicate that many subtitles rely on literal translation, resulting in unnatural expressions, inappropriate register, loss of humor, and reduced readability. Additionally, improper handling of nonverbal cues and sentence segmentation negatively affects audience comprehension. Nevertheless, effective use of adaptation and modulation demonstrates the potential for improving subtitle quality. The study concludes that functional, purpose-oriented translation strategies are essential for producing natural, culturally appropriate, and communicative subtitles in audiovisual media.